Botnet: Classification, Attacks, Detection, Tracing, and Preventive Measures - Jing Liu; Yang Xiao; Kaveh Ghaboosi; Hongmei Deng; Jingyuan Zhang (EURASIP Journal on Wireless Communications and Networking, 2009)
Botnets become widespread in wired and wireless networks, whereas the relevant research is still in the initial stage. In this paper, a survey of botnets is provided. We first discuss fundamental concepts of botnets, including formation and exploitation, lifecycle, and two major kinds of topologies. Several related attacks, detection, tracing, and countermeasures, are then introduced, followed by recent research work and possible future challenges.